ANALISIS DESAIN, TEKNOLOGI DAN PRESTASI TURBIN ANGIN 10 KW - Ginting, Dines (BRIN Publishing, 2007)
Small-scale wind energy conversion systems have been developed and utilized for rural electric generation. Performance and success of the systems strongly depend on available wind power as well as the design and technologies. Recently, that alternative energy technology is more important to support the electric supply and to anticipate continously increase of electric needs. In order to increase the use of that renewable energy technology, a 10 kW wind turbine has been chosen to be developed. Analysis of the wind turbine shows that the design, technologies, and performances are specific and limited to the application and wind power availability. The adaption and improvement is needed for developing the more effective use to the wind turbine. Keywords: Wind energy, energy terbarukan, Turbine angin.